Diffuse Optical Techniques Applied to Wood Characterisation. Issue 4 (August 2013) - Bargigia, Ilaria; Nevin, Austin; Farina, Andrea; Pifferi, Antonio; D'Andrea, Cosimo; Karlsson, Marcus; Lundin, Patrik; Somesfalean, Gabriel; Svanberg, Sune
We propose an optical method for non-invasive characterisation of wood samples based on two optical techniques: time-resolved diffuse optical spectroscopy and gas in scattering media absorption spectroscopy. While the latter is sensitive to gases present inside wood pores, the former extracts information on the bulk material regarding light scattering and absorption. Measurements on spruce samples, cut along different wood fibre directions, are presented to show an example of the advantages of this combined approach: by applying these two non-destructive techniques together, in fact, relevant information on wood such as porosity, permeability and moisture content can be assessed. Furthermore, the chemical composition, internal structure and the anisotropy due to the wood fibres can be investigated.